The South African National War College military history staff ride as a deep learning experience - Jacobs, James Jacobs; Wassermann, Johan (Scientia Militaria - South African Journal of Military Studies, 2021)
In this article, based on a study rooted in interpretivism, the South African NationalWar College military history staff ride, as an education and training method related tothe curriculum of the senior staff programmes since 2002, is discussed. The educationand training process, with specific reference to the staff ride to military battle sites andthe associated application of the theory of operational art, were researched accordingto the tenets of the theory of deep learning. While using the historical–comparativemethod during the staff ride enabled the majority of the students to determine whichviable options were available to the commander, not all students were necessarily ableto relate deep learning to critical thinking. Consequently, in certain instances, surfacelearning tended to dominate simply because that was the educational world into whichthe students had been socialised. Furthermore, the facilitation process did not alwaysfully serve the students by completely weaning them off learning habits associated withsurface learning. Consequently, while being able to claim some deep learning successesusing the staff ride, continuous reflection and educational interventions are neededto maintain the successes achieved and to use these as a building platform for deeplearning during future staff rides.